The Influence of Millennial Market Orientation on Business Performance Moderated By Regional Regulations in Traditional Herbal Medicine SMEs - Artono, Artono; Setiawan, Margono; Surachman, Surachman; Prabandari, Sri Palupi (International Review of Management and Marketing, 2024)
This research aims to analyze how millennial market orientation influences the business performance of traditional medicine SMEs and to what extent local regulations moderate this influence. Using an explanatory approach with quantitative methods, data were collected through questionnaires and analyzed using the partial least squares (PLS) technique to test relationships between variables. The findings reveal that millennial market orientation significantly influences the business performance of traditional medicine SMEs, with a path coefficient of 0.529 and a p-value of 0.000 (< 0.05). This indicates that an increase in millennial market orientation enhances business performance. However, the second hypothesis is not supported. Regression analysis shows a positive relationship between local regulations and millennial market orientation on business performance, but the moderating influence of local regulations is not statistically significant (p 0.242 > 0.05). The practical implication is that traditional medicine SMEs need to enhance millennial market orientation to improve business performance. Understanding the preferences and needs of the millennial market can enhance competitiveness and profitability. Local regulations do not significantly moderate this relationship, so the focus on millennial market orientation should remain a priority without relying on local regulations as a moderating factor.